2014
DOI: 10.2147/ijn.s62263
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced brain delivery of lamotrigine with Pluronic® P123-based nanocarrier

Abstract: Background P-glycoprotein (P-gp) mediated drug efflux across the blood–brain barrier (BBB) is an important mechanism underlying poor brain penetration of certain antiepileptic drugs (AEDs). Nanomaterials, as drug carriers, can overcome P-gp activity and improve the targeted delivery of AEDs. However, their applications in the delivery of AEDs have not been adequately investigated. The objective of this study was to develop a nano-scale delivery system to improve the solubility and brain penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Recently, more attention has focused on P123 due to its biocompatible, safe, and relatively nontoxic properties, particularly, it can suppress the expression of P-gp [34]. Study has reported that lamotrigine loaded P123 NMs can overcome the activity of P-gp to enhance brain penetration of certain antiepileptic drugs via the blood-brain barrier [35]. Consistently, our study confirmed that P-gp was highly expressed in MDR Figure 7.…”
Section: Agingsupporting
confidence: 85%
“…Recently, more attention has focused on P123 due to its biocompatible, safe, and relatively nontoxic properties, particularly, it can suppress the expression of P-gp [34]. Study has reported that lamotrigine loaded P123 NMs can overcome the activity of P-gp to enhance brain penetration of certain antiepileptic drugs via the blood-brain barrier [35]. Consistently, our study confirmed that P-gp was highly expressed in MDR Figure 7.…”
Section: Agingsupporting
confidence: 85%
“…Pluronic copolymers are FDA-approved and have been used to efficiently formulate various drugs for their delivery to the stomach [ 39 ], brain [ 40 , 41 ], liver [ 42 ], and various tumor cells [ 43 47 ]. Additionally, Pluronics conjugated to alendronate, pyrophosphate, and phosphoserine have shown great promise as tooth-targeting systems when used in the micellar formulation of hydrophobic antimicrobial compounds [ 26 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct delivery of drugs into the brain by intracerebral or intracerebroventricular routes are considered important approaches for the management of epilepsy, especially in drug-resistant patients [ 86 ]. Several studies have used nanoformulations for the targeted delivery of antiepileptic drugs to the receptor site via intravenous, oral, intranasal, and transdermal routes [ 87 , 88 ]. Only a few reports can also be found on the NE-based direct nose-to-brain delivery of antiepileptic drugs.…”
Section: Intranasal Nes For Brain Disordersmentioning
confidence: 99%